Gadget Usage Connection With Sleep Patterns Of 12-15 Year Old Teenagers In Wonocolo Village, Kedewan District, Bojonegoro Regency - Mulyani, Sri; Afandi, Agus Ari; Putri, Evita Muslima Isnanda; Utari, Ine Heti Desi (Sean Institute, 2022)
Continuous gadget usage will have a negative impact on teeanager's behavior patterns in their daily lives. Of course, excessive use of gadgets can disrupt sleep patterns in children. Data analysis using Chi-Square test. The results obtained mostly with excessive gadget usage, namely 44 respondents (83%), mostly with poor sleep patterns, namely 41 respondents (77.4%) and there is a relationship between gadget usage and sleep patterns of teenagers aged 12-15 years in the village. Wonocolo, Kedewan District, Bojonegoro Regency in 2022 (ρ = 0.000; r = 0.716).In teenagers with excessive gadget usage, it can lead to poor sleep patterns, and conversely in teenagers with ideal gadget usage, the risk of disturbed sleep patterns will be minimal